Emprunt Comme Procédé D’Enrichissement De la Terminologie du Terrorisme - Igwe, Chidi Nnamdi (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 2006)
The terminology of terrorism has undergone significant lexical enrichment during the pre and post 9/11 period, yet the phenomenon has been understudied by terminologists. As a research project for our doctoral thesis, we undertook to develop the terminology of contemporary terrorism with the dual objective of building a bilingual terminological lexicon (French - English) for the subject field and of determining the degree of lexical creativity by analyzing the field terms according to various processes of morphological formation. In this paper, we shall examine loaning, one of the most productive means of lexical enrichment in the subject field. Résumé La terminologie du terrorisme de la période avant et après le 11 septembre connaît un enrichissement lexical remarquable bien que les terminologues n’y prêtent pas assez d’attention en ce moment. Dans le cadre de notre thèse de doctorat, nous prenons à tâche de développer une terminologie du terrorisme contemporain, la finalité étant de confectionner un lexique terminologique bilingue (français - anglais) du domaine, mais aussi de déterminer le degré de créativité lexicale tout en analysant les termes du domaine selon leurs différents modes de formation. Dans cet article, nous nous consacrerons à l’emprunt, l’un des procédés les plus productifs de l’enrichissement de la terminologie du terrorisme.